Global transmission of prolyliminopeptidase-negative Neisseria gonorrhoeae strains: implications for changes in diagnostic strategies. Issue 1 (10th August 2006) - Unemo, M; Palmer, H M; Blackmore, T; Herrera, G; Fredlund, H; Limnios, A; Nguyen, N; Tapsall, J
Abstract : Background: Species confirmation of Neisseria gonorrhoeae is commonly performed with biochemical kits, rely on the activity of the enzyme prolyliminopeptidase (PIP). This enzyme has previously been considered to be almost universally present in N gonorrhoeae . However, increasing numbers of N gonorrhoeae isolates lacking PIP activity have been identified. Objectives: To investigate the possibility of a widespread transmission of one or several N gonorrhoeae PIP-negative strains among several countries worldwide. Methods: PIP-negative N gonorrhoeae isolates cultured from 2001 to 2004 in Australia, New Zealand and Scotland were comprehensively characterised and compared with previous data from England and Denmark. All isolates were characterised by antibiotic susceptibility testing, serovar determination, pulsed-field gel electrophoresis (PFGE), opa-typing, sequencing of the entire porB gene and N gonorrhoeae multiantigen sequence typing (NG-MAST). Results: Most (83%) of the viable Australian isolates, and all the New Zealand and Scottish isolates were assigned serovar IB-4, with similar antibiograms, nearly identical porB1b gene sequences, identical (ST210) or highly related (ST292, ST1259) NG-MAST STs, and indistinguishable or related PFGE fingerprints as well as opa-types. The isolates showed characteristics indistinguishable or highly related to the previously described English and Danish outbreak strain. Conclusions: A comprehensive characterisation indicates a widespread dissemination, mainly among men who have sex with men (MSM), of indistinguishable and highly related genotypes that have evolved from a single N gonorrhoeae PIP-negative serovar IB-4 strain among several countries worldwide. An increased awareness of PIP-negative N gonorrhoeae strains is crucial and changes in the diagnostic strategies may need to be considered.